Dedoping-induced interfacial instability of poly(ethylene imine)s-treated PEDOT:PSS as a low-work-function electrode. Issue 1 (4th December 2019) - Cai, Wanzhu; Österberg, Thomas; Jafari, Mohammad J.; Musumeci, Chiara; Wang, Chuanfei; Zuo, Guangzheng; Yin, Xiaolong; Luo, Xuhao; Johansson, Jim; Kemerink, Martijn; Ouyang, Liangqi; Ederth, Thomas; et al.
Abstract : Low-work-function PEDOT:PSS electrodes, suitable for organic photovoltaic modules, were achieved by coating PEIx onto the electrode surface. We mapped the physical and chemical processes that occurred at the interface between PEIx and PEDOT:PSS during printing. Abstract : Transparent organic electrodes printed from high-conductivity PEDOT:PSS have become essential for upscaling all-carbon based, low-cost optoelectronic devices. In the printing process, low-work-function PEDOT:PSS electrodes (cathode) are achieved by coating an ultra-thin, non-conjugated polyelectrolyte that is rich in amine groups, such as poly(ethylene imine) (PEI) or its ethoxylated derivative (PEIE), onto PEDOT:PSS surfaces. Here, we mapped the physical and chemical processes that occur at the interface between thin PEIx (indicating either PEI or PEIE) and PEDOT:PSS during printing. We identify that there is a dedoping effect of PEDOT induced by the PEIx. Using infrared spectroscopy, we found that the amine-rich PEIx can form chemical bonds with the dopant, PSS. At lower PSS concentration, PEIx also shows an electron-transfer effect to the charged PEDOT chain. These interface reactions lock the surface morphology of PEDOT:PSS, preventing the redistribution of PSS, and reduce the work function. Subsequent exposure to oxygen during the device fabrication process, on the other hand, can result in redoping of the low-work-function PEDOT:PSS interface, causing problems for printing reproducible devices under ambient conditions.